Wykład o rachubie czasu zawarty w Rygwedadźjotiszawedandze - Monkiewicz, Marta (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych UWr, 2018)
One’s life in ancient India was centered around Vedic rites. In order for the ritual to be celebratedbcorrectly, it was necessary to know the appropriate time for that, that is, to determine thebpropitious time for it drawing upon the position of moon and the sun in the (night)sky. The treatise Ṛgvedajyotiṣavedāṅga is the oldest preserved work containing not only passages proving that astronomical observations were applied at those times, but also that some complex mathematical instructions were employed, especially on the division of time and the setting of meaningful moments of the day depending also on the position of the sun and the moon in the horizon. These times of the day, determined by the calculations and observations, were foundation for determining the appropriate time for the celebration of the Vedic ritual.
Keywords: Ṛgvedajyotiṣavedāṅga; jyotiṣa; nakṣatra